Qatar : 2022 Article IV Consultation-Press Release; and Staff Report. - International Monetary Fund. Middle East and Central Asia Dept.. (Washington, D.C. : International Monetary Fund, 2022)
Swift and decisive policy response to the Covid-19 pandemic has helped to mitigate the health and economic impact of the crisis. Fast vaccination rollout has also strengthened the economy's resilience to new pandemic waves, paving the way for a speedy recovery. As the economy rebounds, a gradual exit from pandemic support measures is underway.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Qatar